Cross-lagged relationship between home numeracy practices and early mathematical skills among Chinese young children - Wei, Wei; Wang, Qi-Yi; Luo, Qin; Li, Yan (Frontiers in Psychology, 2022)
The present study examined the cross-lagged relationship between home numeracy practices (e.g., formal teaching, number games, number application) and early mathematical skills (basic number processing, arithmetic skills) among Chinese young children. One hundred and fifty children (82 boys; Mage = 73.74 months, SD = 3.61 months) were assessed with basic number processing and arithmetic skills at three timepoints during the kindergarten year. Parents reported their parent-child numeracy activities and children’s executive functions. Main results from random-intercept cross-lagged panel models showed that, at the within-family level, earlier basic teaching activities uniquely predicted subsequent basic number processing, while both advanced teaching activities and number game activities at earlier timepoints predicted the following arithmetic skills. These results indicated a unidirectional effect from home numeracy practices on early mathematical skills during the early years.